Voice Behavior: A Systematic Literature Review – A Model of Antecedents and Outcomes - Dhea Rahma Salsabila; Anis Eliyana; Ahmad Rizki Sridadi (LPPM Universitas BSI, 2023)
Despite a large number of voice behavior studies with over 400 artikels published in the last four years, this study provides an integrative and comprehensive review of 43 artikels about voice behavior over 20 years (1998–2022) using the Systematic Literature Review (SLR) research method, and thus the aim of this study is to expand this field in two different ways. First, this study identified the antecedents and outcomes of voice behavior. Second, this study will map the theoretical networks of voice behavior in terms of its antecedents and outcomes. Thus, it is hope that the findings of this study will help researchers and practitioners keep abreast of the growing literature on voice behavior. This study also looks for future research that may advance this area of voice behavior, including theoretical and empirical advances.